Proceedings of the Conference of Central and State Evaluation Organisations Held in New Delhi on 28th July 1999 and their Status Papers - Planning Commission (Planning Commission, 2000)
Planning is the foundation on which the superstructure of development is raised. Fundamental to achieving the specific objectives of development in plan schemes are the target planning, process of implementation and the institutional mechanism governing it. It is the periodic evaluation of the schemes, which bring out their success or failure, their strength and weaknesses by testing the validity of the assumptions inherent in the planning processes, the efficacy of the delivery mechanism and peoples’ participation in the scheme. In short, timely evaluation of the Plan schemes would be diagnostic key to our efforts at economic transformation. Evaluation Machinery has now more than 45 years experience at the Central level and 25 years experience in case of most State Governments. Some State Governments have not yet constituted their Evaluation Machinery.
Programme Evaluation Organization Planning Commission Government of India New Delhi